2020
DOI: 10.1101/2020.11.03.20222810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrospective survey from Vascular Access Team Lombardy Net in COVID-19 era

Abstract: Background: Venous Access Devices (VADs) are the most used device in COVID-19 patients. To the best of our knowledge this is first survey on VADs in COVID-19 era. Objective: Identify catheter related thrombosis (CRT), catheter-related bloodstream infection (CRBSI), and accidental remove of VADs in both COVID-19 positive and COVID-19 free patients. Successive analysis was conducted comparing COVID-19 positive patients with COVID-19 free with inverse probability propensity score weights using simple regression t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In a large-scale retrospective study of vascular access in COVID-19 patients, Gidaro et al found catheter-related thrombosis (CRT) occurred in 42 (1.9%) of cases [48]. In other studies, most identified cases occurred in peripheral veins and in the context of hemodialysis [49][50][51][52][53][54]; rare cases of CRT secondary to central venous catheter thrombosis have also been described [55,56].…”
Section: Catheter-related Thrombosismentioning
confidence: 99%
“…In a large-scale retrospective study of vascular access in COVID-19 patients, Gidaro et al found catheter-related thrombosis (CRT) occurred in 42 (1.9%) of cases [48]. In other studies, most identified cases occurred in peripheral veins and in the context of hemodialysis [49][50][51][52][53][54]; rare cases of CRT secondary to central venous catheter thrombosis have also been described [55,56].…”
Section: Catheter-related Thrombosismentioning
confidence: 99%